The crystal structure of poly(triaqua-(m 2-2,2′-bipyridine-4,4′-dicarboxylato-K 2 O:O′)-bis(m 2-2-2′-bipyridine-4,4′-dicarboxylato-K 4 O,O′:O″:O‴)dierbium(III)) hydrate, C36H26Er2N6O16 - Liu Xu; Zhang Xiao-Yu; Huang Xiao-Wei (Zeitschrift für Kristallographie - New Crystal Structures)
C36H26Er2N6O16, triclinic, P 1− $\overset{-}{1}$ (no. 2), a = 11.3488(3) Å, b = 12.1777(3) Å, c = 14.1863(3) Å, α = 95.054(2)°, β = 103.634(2)°, γ = 101.470(2)°, V = 1848.44(8) Å3, Z = 2, R gt(F) = 0.0297, wRref (F 2) = 0.0645, T = 150 K.